Imaging coral II: Using ultrasound to image coral skeleton - Cleveland, R; Cohen, A; Roy, R; Singh, H; Szabo, T (Springer Verlag, 2004)
We report on imaging of coral skeletal densities using pulse-echo ultrasound. Focused ultrasound transducers with frequencies ranging from 1 to 5 MHz were used to image coral skeletal samples. Each transducer was scanned over the surface of a coral and the reflected signal from the coral was recorded. Post-processing of the ultrasound signal was used to generate images of the acoustic impedance of the coral—a quantity that is related to the density of the coral. The ultrasound images were qualitatively consistent with X-ray images of the coral samples—X-ray absorption is also related to coral density. Both images showed a banding structure related to the annual growth cycle of the coral. The results indicate that ultrasound can be used for nondestructive imaging of coral skeletal structure. The ultimate goal would be an in situ system for quantitatively measuring skeletal densities of live corals underwater. The skeletal density of several massive reef coral species is strongly correlated with ocean temperature. A time series reconstructions of the skeletal density of long lived specimens would provide a history of surface ocean temperatures over time periods extending over several centuries, far beyond the available instrumental record.